Leguminous cover crops and soya increased soil fungal diversity and suppressed pathotrophs caused by continuous cereal cropping - Yu, Shuting; Wang, Tianshu; Meng, Yili; Yao, Shuihong; Wang, Li; Zheng, Haotian; Zhou, Yanzheng; Song, Zewei; Zhang, Bin (Frontiers in Microbiology, 2022)
The enrichment of soil-borne fungal pathogens and a high input of mineral fertilizer in the continuous cropping of cereal crops have raised a concern about soil health deterioration. Conversion of continuous cereal cropping to a legume-involved system alters the soil fungal community. However, when a leguminous cover crop is grown with a succeeding legume grain crop such as soya (Glycine max L. Merril), the effects on the soil fungal community when two legumes are involved in the crop system remain unclear. Thus, the effects of the cover crop on the soil fungal community under a succession of soya and a succession of maize (Zea mays L.) were clarified: a continuous wheat (Triticum aestivum L.)–maize cropping system was converted to new rotation systems with three cover crop treatments: leguminous vetch (Vicia sativa L.), a mixture of vetch and rye (Secale cereale L.), and fallow, succeeded by soya or maize in this study. The soil fungal community at the harvest of soya and maize were determined using high-throughput sequencing of ITS2 amplicons. Compared to a wheat–maize rotation system, all of the new rotation systems that involved leguminous crops or fallow increased the soil fungal diversity and suppressed pathotrophs by reducing the soil NH4+, NO3-, available K, and available P concentrations. Different cover crops changed the fungal community composition, but their effect was overwhelmed by the strong effect of succeeding soya, which induced minor shifts among the cover crop treatments under soya than maize. The Vetch–Soya system exhibited the highest fungal diversity, which have been due to an increase of symbiotrophs. Replacing wheat with mixed vetch and rye most greatly suppressed the pathotrophs, and this suppression effect was stronger when succeeded by maize than by soya. These results showed the short-term benefits of legume–legume succession and legume–cereal mixed cover crops for increasing fungal diversity and suppressing pathotrophs. Further study is needed to examine the long-term effects of Vetch–Soya on the accumulation of legume-associated pathogens.